Sistem Informasi Akuntansi menggunakan Metode Framework for the Application of System Thinking (FAST) - Edi Purnomo; Darya Setia Nugraha (Indonesian Accounting Literacy Journal, 2022)
This study is an accounting information system development using Access 365. The problem discovered was that PT. Ebiz Prima Nusa's accounting information system was insufficient for the scale of the company and not in conformity with financial accounting standards. The goal is to analyze how the accounting information system now in use and to design a suitable accounting information system. The method employed is qualitative, with data gathered through observations, documentation, and interviews. The study is carried out at PT. Ebiz Prima Nusa, a new company that was established in September 2021. Researchers developed a basic application system that can cover the sales, cash receipts, and cash disbursements cycles, as well as the ensuing output, namely financial statements that comply with financial accounting standards in Indonesia.